Performance of Self‑healing Cementitious Mortar with PVA Fiber and SAP - Sukmin Kwon; Sugyu Lee; Hyunuk Kang; Min Kyoung Kim; Sungwun Her; Sungchul Bae; Dong Joo Kim; Juhyuk Moon (International journal of concrete structures and materials, 2024)
Although concrete materials generally exhibit outstanding mechanical properties, it is susceptible against crack formation. It has been reported that narrow cracks (≤ 150 µm) could be naturally sealed in the cement matrix by externally supplied water-induced hydration. However, the crack width of larger than 150 µm is difficult to be sealed without using additional self-healing admixture. In this study, the self-healing cementitious mortar was successfully developed by using a combination of polyvinyl alcohol (PVA) fiber and superabsorbent polymer (SAP), aiming to heal the wide cracks. Although the mechanical properties were slightly reduced, it shows outstanding self-healing performance by using the dual admixtures. A self-healing rate of 60% was observed in the control sample with an initial crack width of 300 µm, while a self-healing rate of nearly 100% was confirmed with suitable SAP and PVA. In addition, it was confirmed that lower hydration degree of self-healing mortar in early stage contributes to the enhanced self-healing performance of developed composite system by internally supplied water from SAP. KCI Citation Count: 0